Efectos de la levadura saccharomises cerevisae, sobre la producción de vacas lecheras (2023)
The main objective of the project was to evaluate the effects of the yeast Saccharomyces cerevisiae on milk production, glucose and body condition of dairy cows from the Bogotá savanna located in Facatativá Cundinamarca. The study was longitudinal with a duration of 60 days, selecting 20 cows that were found in the first 50 days postpartum; divided into two groups, treatment group which will receive Saccharomyces cerevisiae yeast, doce 7 gr/cow/day, supplied within the concentrate and the second group was the control group, which will not receive the product, these cows remained together in the same pasture with the rest of the cows in the herd. Body condition and glucose concentration on days 0, 30 are considered and milk was recorded during the study. The glucose concentrations of the control group were 82.5 mg/dL and of the treatment 83.4 mg/dL (p=1.00) observing that there was no difference between them, the body condition in the control group was 2.79 and treatment of 2.88 (p = 0.446) in which no differences were evident and regarding milk production in the control group were 26.68 L and in the treatment group 22.99 L. The inclusion of the yeast Saccharomyces cerevisiae did not demonstrate any effect on energy metabolism or milk production in grazing dairy cows.